Human-Vehicle Intersection Traffic Lights Timing Optimization Research - Wen Li; Hongying Zhang; Zhaoguo Huang; Chenhui Li (Journal of Advanced Transportation)
The purpose of this research is to find a traffic light timing optimization scheme. During the research, an intersection between Xi’an Mingguang road and the Fourth FengCheng road was chosen to analyze the crossing time distribution of pedestrians who were separated from west-to-the-right-turn vehicles during which the method of breaking off both ends of pedestrian green light signals was used. The VISSIM software was used for traffic simulation, aimed at improving traffic volume and right-turning vehicle average speed for less vehicle queuing delays, less human-vehicle conflicts, and better security for pedestrians without excessive interruption on their street crossing efficiency. The optimal scheme is obtained and the result shows that (1) the number of passing vehicles remains unchanged, with the queuing delay reduced by 5.78% and crosswalk passing speed increased by 19.01% compared with the original one. (2) As the scheme effect is positively correlated with the increase of right turn vehicle numbers, the scheme could be adopted for urban traffic management based on the local situation, which is not only in peak traffic hours but also in the flat peak time to ensure vehicle efficiency and pedestrian safety in the light of “vehicle yielding to pedestrians” regulation. (3) The scheme could also be adopted in cities with no “vehicle yielding to pedestrians” policy for both people-vehicle separation and pedestrian safety when crossing streets.